The Influence of Leadership on Business Performance in a Production Organization (Journal of Universal Excellence, 2026)
Research Question (RQ): How proper leadership influence on business success in production?Purpose: The purpose and goal is to learn what leadership is, what impact it has on work performance in manufacturing and to find out how we can further improve leadership with the help of the EFQM 2020 model.Method: For the purpose of the research, we used a qualitative method. We made a study of professional and scientific references and analyzed the obtained data.Results: The research showed that leadership is one of the criteria of the EFQM 2020 model and an involves factor in achieving sustainable organizational excellence. It is also an always important function of management, where leaders are dedicated to their work and devote a lot of time to employees. It is also important that organizations identify the right people for this function.Organization: The strategic choice and development of the production manager enables better business and greater job performance.Society: Organizations can contribute to a better working climate and long-term positive results by investing in training for leaders in the field of human affairs and self-awareness.Originality: In the research, we limited ourselves to the references that we selected and reviewed.Limitations/Future Research: In the research, we limited ourselves to selected and reviewed references.
Keywords: leadership; organization; excellence; EFQM; working with people; respect; cooperation; sustainability